Topics in Experimental Dynamics Substructuring and Wind Turbine Dynamics, Volume 2 Proceedings of the 30th IMAC, A Conference on Structural Dynamics, 2012 - Mayes, R.; Rixen, D.; Griffith, D.T; De Klerk, D.; Chauhan, S.; Voormeeren, S.N; Allen, M.S (Conference Proceedings of the Society for Experimental Mechanics Series, 2012)
Topics in Experimental Dynamics Substructuring and Wind Turbine Dynamics, Volume 2,  Proceedings of the 30th IMAC, A Conference and Exposition on Structural Dynamics, 2012, the second volume of six from the Conference, brings together 31 contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Experimental Dynamic Substructures Experimental Substructures Focus Group Test Bed - AMPAIR600 Wind Turbine System Substructure Methods Wind Turbine Analytical-Experimental Methods Wind Turbine Sensing and Health Monitoring Wind Turbine Modal Analysis and Identification Techniques.